Freezing of fruits and vegetables : an agribusiness alternative f or rural and semi-rural areas - Barbosa-Canovas, Gustavo V.; Altunakar, Bilge; Mejia-Lorio, Danilo J.; Food and Agriculture Organization of the United Nations (Rome : Food and Agriculture Organization of the United Nations, 2005)
This manual provides information on freezing technology to preserve fruits and vegetables in small-scale operations. Practical examples dem onstrating the application of the technology are given to provide a bet ter understanding of the processes. Compared to other conventional meth ods used in the storage of fruits and vegetables, freezing is the most satisfactory method in terms of quality, process and overall cost. Curr ently, the frozen food market is one the largest sectors in the food in dustry. Industrialized countries dominate the trade in frozen food comm odities, but developing countries can also develop their own frozen foo d industries. Introduction of adequate freezing technology is essential to meet the growing consumer demand for frozen foods in developing cou ntries.
Includes bibliographical references.
Keywords: Fruit -- Preservation; Vegetables -- Preservation; Frozen foods; Frozen fruit; Frozen vegetables